2015
DOI: 10.1016/j.rppede.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Turner syndrome and genetic polymorphism: a systematic review

Abstract: Objective: To present the main results of the literature on genetic polymorphisms in Turner syndrome and their association with the clinical signs and the etiology of this chromosomal disorder. Data sources: The review was conducted in the PubMed database without any time limit, using the terms Turner syndrome and genetic polymorphism. A total of 116 articles were found, and based on the established inclusion and exclusion criteria 17 were selected for the review. Data synthesis: The polymorphisms investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
1
13
0
5
Order By: Relevance
“…This genetic variant was analysed in 109 TS patients and compared with 109 healthy, age‐matched controls. In our study group, PTPN22 was not related with the syndrome ( p = .61, OR 0.33), confirming that this polymorphism has a different effect in different populations and highlighting the importance of genetic background (Liao, Chen, Zhao, & Xie, ; Trovó de Marqui, ). Bearing in mind that polymorphisms act in an additive manner, the ZFAT Ex9b‐SNP10 variant was included in an attempt to explore whether other polymorphic variants can be associated with thyroid autoimmunity risk in TS.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This genetic variant was analysed in 109 TS patients and compared with 109 healthy, age‐matched controls. In our study group, PTPN22 was not related with the syndrome ( p = .61, OR 0.33), confirming that this polymorphism has a different effect in different populations and highlighting the importance of genetic background (Liao, Chen, Zhao, & Xie, ; Trovó de Marqui, ). Bearing in mind that polymorphisms act in an additive manner, the ZFAT Ex9b‐SNP10 variant was included in an attempt to explore whether other polymorphic variants can be associated with thyroid autoimmunity risk in TS.…”
Section: Discussionsupporting
confidence: 66%
“…TS is no exception. However, in 2015, a systematic review of formal studies of polymorphisms associated with the aetiology and clinical manifestations of TS concluded that the evidence is insufficient and more studies are needed to highlight the clinical relevance of this association and the influence of ethnicity (Trovó de Marqui, ). Bianco et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotype-phenotype correlation is not understood [12]. In TS, genetic polymorphisms are associated with clinical features [13]. TS 45X karyotype is most frequent, there is a loss of the paternal X or Y chromosome in meiosis or in early embryogenesis than by loss of the maternal X chromosome [14].…”
Section: Discussionmentioning
confidence: 99%
“…The main general clinical characteristics suggesting the diagnosis of TS include short stature, webbed neck, sexual infantilism, cubitus valgus, gonadal dysgenesis, short metacarpals, shield‐like chest, breast hypertelorism, cardiac and renal malformations, intestinal telangiectasia, and multiple pigmented nevi . Craniofacial stigmata include epicanthic folds, short nose with elevated base and tip, triangular face, micrognathia with small receding chin, low‐set prominent ears, low hairline at the nape of the neck, and compromised craniofacial growth …”
Section: Introductionmentioning
confidence: 99%